Post-synthetic modification of zirconium metal–organic frameworks by catalyst-free aza-Michael additions. Issue 41 (26th September 2018) - Amer Hamzah, Harina; Crickmore, Tom S.; Rixson, Daniel; Burrows, Andrew D.
Abstract : UiO-66-NH2 reacts with acrylonitrile, acrylic acid, methyl acrylate and methyl vinyl ketone leading to post-synthetic modification of the MOF through C–N bond formation. The acrylonitrile-modified MOF undergoes further reaction to form a tetrazolate-modified MOF. Abstract : The reactions of the zirconium MOF [Zr6 O4 (OH)4 (bdc-NH2 )6 ] (UiO-66-NH2, bdc-NH2 = 2-amino-1, 4-benzenedicarboxylate) with the Michael acceptors acrylonitrile (CH2 CHCN), acrylic acid (CH2 CHCO2 H), methyl acrylate (CH2 CHCO2 Me) and methyl vinyl ketone (CH2 CHC(O)Me) led to post-synthetic modification of the MOF through C–N bond formation without loss of crystallinity. The reactions with acrylonitrile and acrylic acid go to completion, yielding [Zr6 O4 (OH)4 (bdc-NHCH2 CH2 CN)6 ] (UiO-66-AN, 1 ) and [Zr6 O4 (OH)4 (bdc-NHCH2 CH2 CO2 H)6 ] (UiO-66-AA, 2 ) respectively, whereas those with methyl acrylate and methyl vinyl ketone are incomplete, yielding [Zr6 O4 (OH)4 (bdc-NH2 )0.66 (bdc-NHCH2 CH2 CO2 Me)5.34 ] (UiO-66-MA, 3 ) and [Zr6 O4 (OH)4 (bdc-NH2 )2.76 (bdc-NHCH2 CH2 C(O)Me)3.24 ] (UiO-66-MVK, 4 ), respectively. The acrylonitrile-modified MOF UiO-66-AN undergoes further reaction with sodium azide in the presence of zinc(ii ) chloride in n -butanol to form the tetrazolate-modified MOF [Zr6 O4 (OH)4 (bdc-NHCH2 CH2 CN)4.74 (bdc-NHCH2 CH2 CN4 H)1.26 ] (UiO-66-TZ, 5 ).